Konsistensi Penerapan Prinsip Syariah Dalam Penjelasan Pasal 2 Undang-Undang No 21 Tahun 2008 Pada Produk BNI Griya Ib Hasanah Di BNI Syariah Cabang Jember - Holil Nawawi (Qolamuna : Jurnal Studi Islam, 2020)
This study aims to reveal the consistency of the application of sharia principles to Griya iB Hasanah products. In this study, two findings were obtained. First, the mechanism includes several stages, namely: applicant analysis, deposit, disbursement of funds and realization (housing construction) are following the murabahah contract and do not deviate from the sharia principles adopted in the BNI Syariah bank. Second, the sharia principles carried out by BNI Syariah Jember Branch on Griya iB Hasanah products are consistent with the explanation of article 2 of Law Number 21 the Year 2008. Keywords: Consistency, Sharia Principles, Gria iB Hasanah.